O avesso da palavra : tese sobre o silêncio e a esperança - Lourete, Suzana de Alvarenga (2024)
The research, in a very general way, focuses on the problem of rationality in recognition and justice theories. Based on the tradition of the Critical Theory of the Frankfurt School, is analyzed the discursive ethics developed in the Theory of Communicative Action, by Jürgen Habermas. In particular, supported by the logical concepts of identity and autonomy, Habermas ends up idealizing a self-referential communication that is not very open to the otherness of other cosmoperceptions about reality. Thus, when we think about community life (politics of the commons) we leave aside interpretations and interactions that do not submit to the principles of Western logic, as expressed in liberal theories. The foundations of this abstraction are in that bourgeois tradition, whose epistemic valorization privileges the processes of rationality, of an autonomous and authentically human structure of thought for interpreting Reality and, consequently, of organizing the Lifeworld. As a colonial legacy, the way of doing critical theory is guided by logical analyzes of social construction, human rights and History itself. Therefore, the sources for its claims to normative legitimacy are abstract concepts, extracted from the Enlightenment idealizations of a human proud of Nature. This structure of thinking is extremely appropriate to capitalism, especially in its current stage. The climatic consequences of the Anthropocene combined with the virtualization of our intersubjective relationships are not unrelated to the evasion of collective spaces and the loss of meaning in political life. Therefore, this research seeks a methodology that is capable of exploring this literate world of Western philosophy inside out; in an attempt to understand how silenced ways of life are inscribed in time/history as “unsuspected philosophies” and manifest themselves in the Lifeword through Enchantment. Finally, it is argued that the political management of affections is not guided by the liberal ideology of dialectical recognition, but by the affective capacity of a collective and situated subjectivity, whose consciousness-of-us is rooted in Belonging. This time, the Ethics of Enchantment manifests itself in the Lifeword as modes of everyday nanoresistance and the implementation of Justice